2022
DOI: 10.1155/2022/1450756
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel DNA Algorithm for Solving the Quota Traveling Salesman Problem Based on Biocomputing Model

Abstract: The quota traveling salesman problem (QTSP) is a variant of the traveling salesman problem (TSP), which is a classical optimization problem. In the QTSP, the salesman visits some of the n cities to meet a given sales quota Q while having minimized travel costs. In this paper, we develop a DNA algorithm based on Adleman-Lipton model to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…However, the field of biocomputing truly began to take shape in the 1990s, with the advent of DNA computing. The pioneer of this field was Leonard Adleman, a computer scientist from the University of Southern California [37]. In 1994, Adleman published a groundbreaking paper in which he demonstrated that DNA could be used to solve a well-known mathematical problem, the seven-point Hamiltonian path problem, also known as the "traveling salesman" problem.…”
Section: History Of Biocomputersmentioning
confidence: 99%
“…However, the field of biocomputing truly began to take shape in the 1990s, with the advent of DNA computing. The pioneer of this field was Leonard Adleman, a computer scientist from the University of Southern California [37]. In 1994, Adleman published a groundbreaking paper in which he demonstrated that DNA could be used to solve a well-known mathematical problem, the seven-point Hamiltonian path problem, also known as the "traveling salesman" problem.…”
Section: History Of Biocomputersmentioning
confidence: 99%